Respiratory symptoms and occupation: a cross-sectional study of the general population - Smit Henriëtte A; Kromhout Hans; Heederik Dick; Vermeulen Roel (BMC, 2002)
Abstract Background This study focused on respiratory symptoms due to occupational exposures in a contemporary general population cohort. Subjects were from the Dutch Monitoring Project on Risk Factors for Chronic Diseases (MORGEN). The composition of this population enabled estimation of respiratory risks due to occupation from the recent past for both men and women. Methods The study subjects (aged 20-59) were all inhabitants of Doetinchem, a small industrial town, and came from a survey of a random sample of 1104 persons conducted in 1993. A total of 274 cases with respiratory symptoms (subdivided in asthma and bronchitis symptoms) and 274 controls without symptoms were matched for age and sex. Relations between industry and occupation and respiratory symptoms were explored and adjusted for smoking habits and social economic status. Results Employment in the 'construction' (OR = 3.38; 95%CI 1.02 - 11.27), 'metal' (OR = 3.17; 95%CI 0. 98 - 10.28), 'rubber, plastics and synthetics' (OR = 6.52; 95%CI 1.26 - 53.80), and 'printing' industry (OR = 3.96; 95%CI 0.85 - 18.48) were positively associated with chronic bronchitis symptoms. In addition, the 'metal' industry was found to be weakly associated with asthma symptoms (OR = 2.59; 95%CI 0.87 - 7.69). Duration of employment within these industries was also positively associated with respiratory symptoms. Conclusion Respiratory symptoms in the general population are traceable to employment in particular industries even in a contemporary cohort with relatively young individuals.